Emily Brontë and German Romanticism: An Analysis of the Imagery of 'Night' in Emily Brontë's and Novalis's Writings. (3rd July 2019) - Zhao, Jingjing
Abstract : Since the publication of Wuthering Heights in 1847, critics have long recognized the influence of British writers on Emily Brontë, such as Wordsworth, Byron and Shakespeare. In recent years, the possible influence of German Romanticism has also been noted by critics such as Maggie Allen and Elisha Cohn. The extent to which Emily Brontë was acquainted with German Romanticism still waits to be investigated in more depth and detail. In this article, I seek to examine this issue by introducing German poet and philosopher Novalis's work Hymns to the Night and the Fragment and making a textual comparison between Novalis's writings and Emily Brontë's novel and lyrical work. Through an examination of the imagery of 'Night', along with a series of related concepts such as Dream, Vision, Slumber and Death in these two authors' writings, I explore Emily Brontë's acquaintance with, and understanding of, German Romantic ideology on a more comprehensive scale than has been done heretofore.